Dynamic compressive behaviour of sandwich panels with lattice truss core filled by shear thickening fluid. (September 2020) - Gu, Z.P.; Wu, X.Q.; Li, Q.M.; Yin, Q.Y.; Huang, C.G.
Highlights: A hydrodynamic constitutive model for STF is employed to describe the complex dynamic behaviour. An analytical model is developed for describing the dynamic squeezing behaviour of non-Newtonian fluids. The strong interaction between the SPLTC and the STF during the fast flow of the STF near the periphery is obtained. The effects of shear thickening behaviour on the dynamic response of the SPLTC-STF are obtained by the FSI simulation. Abstract: The compressive behaviour of sandwich panels with lattice truss core filled by shear thickening fluid (SPLTC-STF) at high strain-rates is performed analytically and numerically. Firstly, a hydrodynamic constitutive model for the shear thickening fluid (STF) involving shear thinning, shear thickening, and hydrostatic compressibility is undertaken to describe the dynamic behaviour of the STF. Then an analytical model based on the squeezing flow of viscous fluids is proposed. The squeezing resistance of the STF between the two panels of the SPLTC under various loading velocities is analysed using a fluid-structure interaction (FSI) simulation, by which the constitutive parameters of the STF are obtained. Finally, the dynamic response of the SPLTC-STF involving buckling and post-buckling of core struts in the STF is investigated using the FSI method. The enhanced energy absorption capacity of the SPLTC-STF observed in Ref [1] is numerically interpreted. The effects of shear thickening behaviour of STF on the dynamic response of SPLTC-STF are predicted, providing a method of optimal design for STF filled sandwich panels over a wide range of impulse loadings for dynamic energy absorption. Graphical abstract: Image, graphical abstract